Materialism and envy as mediators between upward social comparison on social network sites and online compulsive buying among college students - Ling, Yi; Gao, Bin; Jiang, Bo; Fu, Changqing; Zhang, Juan (Frontiers in Psychology, 2023)
Upward social comparison on Social Network Sites (SNS) might be positively related to online compulsive buying; however, there is little understanding of the mechanism of this relationship. In this study, we explored the effect of upward social comparison on SNS on online compulsive buying, and whether this effect is mediated by materialism and envy. A total of 568 Chinese undergraduates (mean age = 19.58 years, SD = 1.43) were recruited to complete a survey that included Upward social comparison on SNS Scale, Materialism Scale, Envy Scale, and Online compulsive buying Scale. The results revealed that upward social comparison was positively linked to online compulsive buying. Additionally, materialism and envy completely mediated this relationship. Our findings suggest that upward social comparison has a positive influence on college students’ online compulsive buying and that this influence is formed through a combination of cognitive factors (materialism) and affective factors (envy). This discovery not only clarifies the underlying mechanism but also proposes a potential way of alleviating online compulsive buying.